Relationships between the Psychoemotional State of Middle-Aged People and their Physical Activity Levels (Baltic Journal of Sport and Health Sciences, 2020)
Background. Constantly accelerating pace of life, heavy workloads, and new technologies coming into our lives lead to mental health problems - stress, anxiety, and depression, which causes uncontrollable physical health problems. The relationship between individual PA domains and physical activity intensity in middle-aged individuals as well as their psycho-emotional status have not been sufficiently explored. The aim of the study was to determine the relationship between psycho-emotional state and physical activity levels in middle-aged people.Methods. The epidemiological method was chosen for the study. The chosen method of data collection was an anonymous questionnaire survey.Results. Assessing the psycho-emotional state of the subjects, we found that 17.8% of women and men studied were experiencing stress. More women (45%) than men (27.5%) experienced nervous tension, and more men (25.5%) than women (13.7%) experienced stress. High levels of physical activity were found in more than 2/3 of the subjects (73.5%). The distributions of women and men did not differ much according to the level of physical activity (74.3, 72.0%).Conclusion. A higher level of physical activity was associated with a better assessment of nervous tension and stress – more physically active individuals experience less nervous tension and stress. People who spent more time sitting on weekdays and at weekends experienced more nervous tension and stress.Keywords: physical activity levels, psychoemotional state, sedentary lifestyle, physically active lifestyle, nervous tension and stress.